PENGARUH PENGELASAN LOGAM BERBEDA PLAT SS 400 DENGAN PLAT SUS 304 TERHADAP SIFAT MEKANIS - Hamdan Faozi; Sri Hastuti (POLITALA PRESS, 2025)
Metal welding technology used today can connect two different types of metals. The welding is still often found with welding defects, the problems that are often faced are differences in melting points, expansion coefficients, physical, and mechanical properties. The purpose of the research was to determine the effect of strong current variation between low carbon steel SS 400 and SUS 304 stainless steel on mechanical properties. This research method uses experimental, GTAW welding strong variations of currents 60 A, 80 A, and 100 A. The results of this study concluded that the strength of the current affects the tensile strength, and violence. The highest tensile strength is 346.63 MPa with a strain of 9.52 % and the modulus of elasticity is 36.59 MPa at a current strength of 100 A. This is due to the strong difference in currents resulting in different inputs and heat distributions in each specimen. The hardness test results show that specimens with strong current variations of 100 A have the highest hardness level of both the weld region, HAZ, and parent metal, rather than with strong current specimens of 60 A and 80 A, this is because the greater the welding ampere will increase the strength of the hardness.